Style : the art of writing well - Lucas, F. L. (Frank Laurence), 1894-1967 (Harriman modern classics, 2012)
Lost for almost forty years, this guide to recognising and writing stylish prose was written by a Cambridge don and veteran of Bletchley Park. Imbued with a lifetime of wit and wisdom, it retains its power today. Writing forcefully and persuasively has never mattered so much - this book is the perfect guide for the busy, the ambitious, and the creative. With unique authority and good humour, the author takes us through his ten points of effective prose style and provides a tour of some of the best (and worst) that has been written in a number of languages and literatures. Wry, perceptive and rich in quotation and anecdote, the book reads like a personal conversation on the art of writing well - with a master of the art. --